Effect of apixaban compared with warfarin on coagulation markers in atrial fibrillation. Issue 3 (12th September 2018) - Christersson, Christina; Wallentin, Lars; Andersson, Ulrika; Alexander, John H; Alings, Marco; De Caterina, Raffaele; Gersh, Bernard J; Granger, Christopher B; Halvorsen, Sigrun; Hanna, Michael; Huber, Kurt; Hylek, Elaine M; et al.
Abstract : Objectives: Compare the effect of apixaban and warfarin on coagulation and primary haemostasis biomarkers in atrial fibrillation (AF). Methods: The biomarker substudy from the Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation trial included 4850 patients with AF randomised to treatment with apixaban or warfarin. Sixty per cent of patients used vitamin K antagonist (VKA) within 7 days before randomisation. Prothrombin fragment 1+2 (F1+2), D-dimer, soluble CD40 ligand (sCD40L) and von Willebrand factor (vWF) antigen were analysed at randomisation and after 2 months of study treatment. Results: In patients not on VKA treatment at randomisation, F1+2 and D-dimer levels were decreased by 25% and 23%, respectively, with apixaban, and by 59% and 38%, respectively, with warfarin (p<0.0001 for treatment differences for both). In patients on VKA at randomisation, F1+2 and D-dimer levels increased by 41% and 10%, respectively, with apixaban and decreased by 37% and 11%, respectively, with warfarin (p<0.0001 for treatment differences for both). sCD40L levels were slightly increased at 2 months, regardless of VKA or randomised treatment. Apixaban and warfarin also both reduced vWF antigen regardless of VKA treatment. The efficacy (stroke) and safety (bleeding) of apixaban compared with warfarin was similar irrespectively of biomarker levels at 2 months. Conclusions: Treatment with apixaban compared with warfarin for stroke prevention in patients with AF was associated with less reduction in thrombin generation and fibrin turnover. This effect of apixaban could contribute to the clinical results where apixaban was superior to warfarin both in stroke prevention and in reducing bleeding risk. Trial registration number: NCT00412984.